Evidence of WW and WZ production with lepton+jets final states in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (American Physical Society (APS), 2009)
We present first evidence for WW+WZ production in lepton+jets final states at a hadron collider. The data correspond to 1.07fb-1 of integrated luminosity collected with the D0 detector at the Fermilab Tevatron in pp̄ collisions at s=1.96TeV. The observed cross section for WW+WZ production is 20.2±4.5pb, consistent with the standard model and more precise than previous measurements in fully leptonic final states. The probability that background fluctuations alone produce this excess is <5.4×10-6, which corresponds to a significance of 4.4 standard deviations. © 2009 The American Physical Society.